Pengembangan Media Smart Dental Box Terhadap Pemeliharaan Kesehatan Gigi Anak Usia 5-6 Tahun Di TK As-Shofa Kecamatan Tembilahan Hulu - Siti Humaira; Zulkifli N; Defni Satria (Departement of Mathematics Education, 2023)
The independence of children in maintaining dental health, of course, requires knowledge and experience that they get directly through the five senses in their daily activities. This study aims to improve maintenance of dental health in children aged 5-6 years. This study uses a development model with R&D method with the research subjects being students. The types and sources of research data are primary data and quantitative descriptive questionnaires. The research results were validated by validators, namely media experts and material experts. The result of research on the development of smart dental box media can be categorized as “very feasible” with an overall percentage of material experts 91%, media experts 90%, professional educator 92% and product trial results 95%. Based on the results of the study, it can be concluded that smart dental box media is effective and feasible to help maintain dental health for children aged 5-6 years at As-Shofa Kinderganten, Tembilahan Hulu Disctrict.